Physiological profile of elite triathletes: A comparison between young and professional competitors - Diaz, V.; Zapico, A. G.; Peinado, A. B.; Alvarez, M.; Benito, P. J.; Calderon, F. J. (Journal of Human Sport & Exercise, 2009)
The aim of the present work was to compare the cardiorespiratory response of two high level groups of triathletes of different age during a simulation of a cycling-running succession. The two groups, G1 (n=6; age 23.8 ± 5.6 years; weight 71.2 ± 8.7 kg; height 180.0 ± 8.8 cm) and G2 (n=9; age 15.2 ± 0.7 years; weight 60.2 ± 6.8 kg; height 173.6 ± 6.4 cm) performed two tests in a random order. Trial 1 (C-R) consisted of 30 min cycling with a load corresponding to the ventilatory threshold previously calculated, followed by a 3000 m run at the highest possible intensity around a 400 m track. Trial 2 (R), consisted of a 3000 m run at the maximum intensity possible only. The G1 subjects took less time to complete the distance (591.2 compared to 669.1 s for the G2 subjects in the C-R setting, and 584.6 vs. 645.5 s in the R setting). In addition, the G1 subjects showed a more adapted cardiorespiratory response than the G2 subjects. In conclusion, the results show a profile in terms of cardiorespiratory response and performance for senior and young triathletes highly trained.